Entrevista al Dr. Eugenio Beltrán-Aguilar, Director Asociado del Centro Colaborador de la Organización Mundial de la Salud (OMS) en la Universidad de Nueva York - Arana Sunohara, Ana (2020)
Eugenio Beltrán-Aguilar shares in this interview his vision of the advances and pending challenges in Latin America regarding public health, research and technological development in the context of the pandemic by COVID-19. It highlights the importance of carrying out epidemiological studies and institutionalizing epidemiological surveillance systems to generate up-to-date and quality information that serves to support public policies in the face of persistent problems such as dental caries and new challenges such as oropharyngeal cancer associated with human papillomavirus (HPV) infection. It also analyzes the impact of the pandemic on dental education and dental practice, while pointing out routes for advanced research and to improve our knowledge on the possible impacts of the pandemic on the population. All this, in a weakening context of multilateral public health organizations.